Analysis of hardness in the adamantine surface before engraving with flavored beverages : Comparison with the healthy enamel - Lazo, Gabriel Eduardo (2022)
The consumption of different beverages is part of the dietary habits of the population. The pH can act as an erosive agent of the enamel, while the presence of trace elements in the juice can favor damage or act as cariostatic agents. Various soft drinks have pH values below the critical pH of enamel. The aim was to identify the mechanical properties of the microstructure of healthy enamel exposed to non- alcoholic beverages, at the level of prisms and types of enamel, through microhardness tests. Surface hardness after treatment with flavored beverages was recorded in healthy and treated enamel in the radial zone, with Hunter Schreger bands, and in prismatic enamel.